THE IMPACT OF E-LEARNING PLATFORMS ON STUDENT PERFORMANCE IN RURAL NIGERIAN SCHOOLS - Sheik Mohamed S.H.; Sam Hermansyah (CV. Fahr Publishing, 2024)
This study examines the impact of e-learning platform usage on student academic performance in rural Nigerian schools. A descriptive quantitative method was employed, involving 240 respondents from six junior and senior secondary schools. Data were collected using structured questionnaires and analyzed through descriptive statistics and Pearson’s correlation tests. Results revealed that students who consistently accessed e-learning platforms achieved significantly higher academic scores than non-users. Additionally, learners cited major benefits such as flexible learning and access to visual content that enhanced understanding. However, the study also identified key barriers including infrastructural deficits, limited teacher readiness, and lack of technical support. The study concludes that while e-learning holds strong potential for improving educational quality in rural areas, its success depends on targeted investments in infrastructure and teacher training programs.